Estudo de localização de centrais termoelétricas solares de grande porte no estado de Minas Gerais (Revista Espinhaço, 2014)
Solar energy is gaining spacein world’s context, however, in Brazil, is not yet explored in large projects. Although, it is known that the country has areas with direct irradiation of high intensity and low seasonality factor, especially in semiarid and particularly in the North and Northeast of Minas Gerais. This article aims to assess the location for installation of thermal power plants in the state, using the technology of Geographical Information System. We identified levels of irradiation promising for generating solar energy reaching the value of 2200-2400 kWh/m²/year for the semiarid region of Minas Gerais. These regions have flat areas, availability of water resources, low agricultural potential and good coverage of transmission lines. Considering these relevant variables to the classification we found six promising regions (Janaúba, Januária, Pirapora e Unaí, Pirapora e Paracatu, Curvelo e Três Marias, Patrocínio e Araxá). It should be emphasized that this potential can be exploited in the medium term, with the depletion of other energy sources.
Keywords: solar power; solar thermal power; geographic information system